Ologen Implantation versus Conjunctival Autograft Transplantation for Treatment of Pterygium - Xiuping Chen; Fei Yuan (Journal of Ophthalmology)
Purpose. To evaluate the effectiveness and safety of Ologen implantation versus conjunctival autograft transplantation for primary pterygium. Methods. A retrospective case-series analysis. Thirty-one eyes of 29 patients were included in the Ologen group and 42 eyes of 35 patients in the autograft group. The patients were followed up for 1 year and evaluated for slit-lamp biomicroscopy, intraocular pressure, and adverse events. Recurrence rate, complications, and final appearance of the cases were evaluated prospectively. Result. At 1 year after operation, 2 eyes recurred (6.5%) in the Ologen group and 4 eyes recurred (9.52%) in the autograft group. There was no statistically significant difference between both groups (P=0.157, χ2 = 3.781). There was no occurrence of serious complications. Two eyes among the 31 eyes of the Ologen group were conjunctivitis; the incidence of complications was 6.45% (2 eyes). There was conjunctivitis in 3 eyes of the autograft group, 1 eye complicated with symblepharon, and 1 eye with conjunctival granuloma; the incidence of complications was 11.90% (5 eyes), and there was no statistically significant difference between both groups (P=0.094). The conjuntiva was less vascular and inflamed at 1 month postoperatively in the Ologen group than in the autograft group. Conclusions. Ologen transplantation was technically easier, provided short operative time compared with conjunctival autograft transplantation, and preserved healthy conjunctiva with less complication and less recurrence; it may be a new, safe, and effective alternative for improving the short-term success rate of primary surgery.